IMPLEMENTASI IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) DALAM PELAKSANAAN PENILAIAN KINERJA KARYAWAN (PNS) (Studi pada Kementerian Pekerjaan Umum Dan Perumahan Rakyat, SNVT PJPA Pemali-Juana PPK PAT dan PPK PAB) - Nugraha, Nur Chaida; Yuniawan, Ahyar (Diponegoro Journal of Management, 2017)
This study aims to examine the implementation of performance appraisal at the Ministry of Public Works and Public Housing, SNVT PJPA Pemali-Juana PPK  PAT  and  PPK  PAB. Employee performance appraisal  is  an  attempt  to measure the level of employee productivity. A good performance appraisal will elicit the motivation of its employees, which then creates confidence in management, so as to improve employee productivity.This study only uses performance appraisal as an independent variable. In this research, 50 civil servants involved as a questionnaire of respondents by census method. The data test technique used in this research includes validity test with factor analysis, reliability test, gap, and Importance and Performance Analysis (IPA). IPA is a research method by comparing the level of importance with the level of implementation.The results of this study indicate that the most important assessment process   in   the   implementation   of   performance   appraisal   and   integrity improvement  is  least  important.  Based  on  the  results  of  this  study,  the most important attributes require an increased priority to be done in order to remain competitive. Meanwhile, attributes that are considered less important do not require temporary fixes, if necessary ignored or omitted.